Comparison of Patient Reported Outcome Measurement Information System With Neck Disability Index and Visual Analog Scale in Patients With Neck Pain. Issue 3 (1st February 2019) - Moses, Michael J.; Tishelman, Jared C.; Stekas, Nicholas; Jevotovsky, David S.; Vasquez-Montes, Dennis; Karia, Raj; Errico, Thomas; Buckland, Aaron; Protopsaltis, Themistocles S.
Abstract : Study Design: A retrospective analysis of a patient-reported outcomes database from a single institution from December 2016 to April 2017. Objective: To validate the association of Patient Reported Outcome Measurement Information System (PROMIS) with Neck Disability Index (NDI) in patients with neck pain and examine each instruments ability to capture concomitant arm pain and concomitant back pain. Summary of Background Data: PROMIS has been increasingly utilized and its computer adapted testing methodology improves assessment of pain and disability. However, literature is lacking regarding how these instruments perform in neck pain patients with concomitant arm pain or back pain. Methods: Inclusion criteria were age >18 years and a primary complaint of neck pain. The NDI; Visual Analog Scale (VAS) back, neck, arm, and leg; and PROMIS physical function, pain intensity, and pain interference questionnaires were administered. Propensity score matching was performed to compare patients with high and low back and arm pain by controlling for neck pain. Bivariate correlations and independent samples t tests were performed to assess linear relationships and compare back and arm pain groups with PROMIS. Results: Approximately, 130 patients were included. NDI correlated strongly to PROMIS physical function (r = −0.771, P  < 0.001), pain intensity (r = 0.605, P  < 0.001), and pain interference (r = 0.786, P  < 0.001). VAS neck and arm pain also correlated to the PROMIS pain intensity instrument (VAS neck: r = 0.642, P  < 0.001; VAS arm: r = 0.376, P  < 0.001). After matching for neck pain, the high and low back pain groups each included 32 patients. There were significant differences in PROMIS physical function when high and low back pain groups were compared (39.07 vs. 43.68, P  = 0.031). No significant difference was found for any outcome metric for high and low arm pain groups. Conclusion: PROMIS instruments are capable of characterizing pain and disability in patients with neck pain and are sensitive to disability in regions adjacent to the neck. Level of Evidence: 3 Abstract : Patient Reported Outcome Measurement Information System, computer adaptive testing, has been incorporated into physician assessment of pain and disability in various specialties and the present study demonstrates its instruments are capable of characterizing pain and disability in patients with neck pain and are sensitive to disability in regions adjacent to the neck.